Effect of N3-Methyladenine and an Isosteric Stable Analogue on DNA Polymerization. (23rd August 2010) - Settles, Samuel; Wang, Ruo-Wen; Fronza, Gilberto; Gold, Barry
Abstract : N3-methyladenine (3-mA) is a cytotoxic lesion formed by the reaction of DNA with many methylating agents, including antineoplastic drugs, environmental agents and endogenously generated compounds. The toxicity of 3-mA has been attributed to its ability to block DNA polymerization. Using Me-lex, a compound that selectively and efficiently reacts with DNA to afford 3-mA, we have observed in yeast a mutational hotspot at the5 ′ -terminus of an A4 tract. In order to explore the potential role of sequence-dependent DNA polymerase bypass of 3-mA, we developed an in vitro system to prepare 3-mA modified substrates using Me-lex. We detail the effects of 3-mA, its stable isostere analogue, 3-methyl-3-deazaadenine, 3-deazaadenine and an THF abasic site on DNA polymerization within an A4 sequence. The methyl group on 3-mA and 3-methyl-3-deazaadenine has a pronounced inhibitory effect on DNA polymerization. There was no sequence selectivity for the bypass of any of the lesions, except for the abasic site, which was most efficiently by-passed when it was on the5 ′ -terminus of the A4 tract. The results indicate that the weak mutational pattern induced by Me-lex may result form the depurination of 3-mA to an abasic site that is bypassed in a sequence dependent context.